The Influence of the Audit Committee, Profitability, and Company Size on Audit Delay - Ivanti, Pramita Amanda; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
The purpose of this study is to determine the Influence of Audit Committee, Profitability, and Company Size on Audit Delay in Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023. This study uses a quantitative method to identify the influence of one variable on another. The data used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX). The data of this study used SPSS software version 26 with descriptive statistical analysis tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the analysis carried out, the author can draw conclusions that: (1) The audit audit committee variable has a beta of 0.008 and a significance value of 0.006 < 0.05. Therefore, the hypothesis (H1) that states that the audit committee has an effect on audit delay in this variable is accepted. (2) The Profitability variable has a beta of 0.420 and a significance value of 0.00 < 0.05. Therefore, the hypothesis (H2) that states that profitability affects audit delay in this variable is accepted. (3) The Company Size variable has a beta of .906 and a significance value of 0.00 < 0.05. So, the hypothesis (H2) that states that the size of the company affects the audit delay in this variable is accepted.